Radix Paeoniae Alba attenuates Radix Bupleuri-induced hepatotoxicity by modulating gut microbiota to alleviate the inhibition of saikosaponins on glutathione synthetase - Congcong Chen; Wenxia Gong; Junshen Tian; Xiaoxia Gao; Xuemei Qin; Guanhua Du; Yuzhi Zhou (Elsevier, 2023)
Radix Bupleuri (RB) is commonly used to treat depression, but it can also lead to hepatotoxicity after long-term use. In many anti-depression prescriptions, RB is often used in combination with Radix Paeoniae Alba (RPA) as an herb pair. However, whether RPA can alleviate RB-induced hepatotoxicity remain unclear. In this work, the results confirmed that RB had a dose-dependent antidepressant effect, but the optimal antidepressant dose caused hepatotoxicity. Notably, RPA effectively reversed RB-induced hepatotoxicity. Afterward, the mechanism of RB-induced hepatotoxicity was confirmed. The results showed that saikosaponin A and saikosaponin D could inhibit GSH synthase (GSS) activity in the liver, and further cause liver injury through oxidative stress and nuclear factor kappa B (NF-κB)/NOD-like receptor thermal protein domain associated protein 3 (NLRP3) pathway. Furthermore, the mechanisms by which RPA attenuates RB-induced hepatotoxicity were investigated. The results demonstrated that RPA increased the abundance of intestinal bacteria with glycosidase activity, thereby promoting the conversion of saikosaponins to saikogenins in vivo. Different from saikosaponin A and saikosaponin D, which are directly combined with GSS as an inhibitor, their deglycosylation conversion products saikogenin F and saikogenin G exhibited no GSS binding activity. Based on this, RPA can alleviate the inhibitory effect of saikosaponins on GSS activity to reshape the liver redox balance and further reverse the RB-induced liver inflammatory response by the NF-κB/NLRP3 pathway. In conclusion, the present study suggests that promoting the conversion of saikosaponins by modulating gut microbiota to attenuate the inhibition of GSS is the potential mechanism by which RPA prevents RB-induced hepatotoxicity.